Prediction of esophageal varices in cirrhosis by using splenic stiffness measurement - Behera, Sanatan; Behera, Manas Kumar; Jena, Sushanta Kumar; Mahapatro, Arupam (International Journal of Research in Medical Sciences, 2024)
Background: Predicting esophageal varices in cirrhosis using the measurement of splenic stiffness is an exciting area of study. Vein enlargement in the lower esophagus, known as varices, is a common symptom of cirrhosis caused by portal hypertension. These varicose veins are potentially fatal since they bleed easily. The present study aims to predict the OV in cirrhosis patients by splenic stiffness in and around this region. Methods: After receiving permission from the Institutional Ethics Committee, the study was performed. The present study authors measured splenic stiffness and liver stiffness by using FibroScan in 112 consecutive cirrhotic patients who met the inclusion criteria. Patients were also assessed by hepatic venous pressure gradient (HVPG), upper gastrointestinal endoscopy, liver stiffness, liver spleen diameter to platelet ratio score, and platelet count to spleen diameter ratio. Results: Among 112 patients enrolled, 64 patients had valid liver stiffness and splenic stiffness measurement, and 64 patients had EV (small, n=23 and large n=42). There was a significant difference in median liver stiffness (54.2 vs. 21.3 kPa, p<0.05), splenic stiffness (56.1 vs. 30 kPa, p<0.05), liver spleen diameter to platelet ratio score (6.3 vs. 2.7, p<0.05), and platelet count to spleen diameter ratio (798 vs 1,241, p<0.05) between patients with OV and those without OV. Conclusions: Non-invasive markers, such as splenic stiffness, may help identify individuals with cirrhosis who are at risk of having esophageal varices, especially large ones, and who are at risk of bleeding, the study’s authors conclude.